Perancangan aplikasi E-wallet berbasis website - Angga Aditya, Anak Agung Gede Agung; Mahendra, Ida Bagus Made (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
In this modern era many new technology have been create for support human life. One of them is electronic wallet, where this technology can save electronic money. Electronic wallet make life easier, like can help for transaction in shopping and another transaction. User also can do topup, transfer, and withdraw from electronic wallet. This electronic wallet win run in website, create using JavaScript Framework that is Vue.js and database using GraphQL..